Physiological and Biochemical Responses of Plants to Rooftop and Ground-level Conditions in Urban Green Spaces - Mehak Shehzad; Adnan Younis; Kashf Mehmood; Alanoud T. Alfagham; Saud Alamri; Afroz Rais; Shahbaz Khan (HortScience)
An understanding of plant adaptation to rooftop environments is essential for improvising urban greening strategies; however, limited research has systematically examined the physiological and biochemical responses of plants at urban rooftops. This study addressed this gap by evaluating physiological and biochemical alterations of six herbaceous perennial species, Rosa hybrids, Murraya paniculata, Cestrum nocturnum, Pittosporum tenuifolium, Duranta, and Hibiscus rosa sinensis, cultivated in an intensive rooftop garden environment vs. optimal ground conditions. These species, acclimatized to the local climate of Pakistan, were assessed to determine the transpiration rate, photosynthetic rate, chlorophyll contents, and respiration rate using on-site measurements and standardized leaf tissue analyses. The results demonstrated significant differences in physiological and biochemical parameters between rooftop and ground-level plants. Seasonal variations and elevation profoundly influenced plant physiology and significant biochemical alterations observed in response to rooftop conditions. Photosynthetic and transpiration rates were reduced by up to 30% in winter under low light conditions, while summer conditions led to a 25% increase in transpiration rates for rooftop plants. Ground-level plants exhibited the highest respiration rates during the summer season. A leaf analysis revealed that rooftop-grown plants exhibited higher pH levels and 15% increased chlorophyll and ascorbic acid contents but 20% lower water use efficiency compared with their ground-level counterparts. Despite this, rooftop plants showed a 10% higher air pollution tolerance index. Pearson’s correlation analysis confirmed a strong positive relationship between most biochemical parameters and physiological activities with increased elevation, except for relative water content, which exhibited a negative correlation under rooftop conditions. The results indicated that those plants on rooftops exhibited reduced water use efficiency compared with that of ground-level plants undergoing distinct physiological and biochemical adaptations and showed more resilience to the pollution index in response to urban rooftop conditions. These findings provide new insights into plant adaptability in urban environments and can transform future strategies for sustainable urban greening and species selection in roof garden systems.